Reconfiguring the Archive: Relationality and Discovery in the Africa Multiple Interactive Research Atlas (AMIRA) - Madore, Frédérick (2026)
The Africa Multiple Interactive Research Atlas (AMIRA, https://data.africamultiple.uni-bayreuth.de/) is the public access point for the research (meta)data of the Africa Multiple Cluster of Excellence at the University of Bayreuth (Germany). Built on Omeka S by the Cluster's Digital Research Environment (DRE), it brings together nearly 4,000 research items, more than 90 projects, some 1,600 people, and close to 600 organisations across 39 countries and 28 languages. The collections come from the five Africa Multiple Research Centres — University of Bayreuth, University Joseph Ki-Zerbo, University of Lagos, Moi University, and Rhodes University — and their partners. Curation is shared: each centre describes the data it knows best, while Bayreuth maintains a metadata layer that points to data held locally rather than relocating it, following the FAIR and CARE principles. This paper presents AMIRA as a case study in what it means to reimagine a digital collection built on relationality. Rather than discrete records, the atlas foregrounds connections between entities: knowledge graphs linking people, projects, places, and publications; collaboration networks; and "discursive communities" that cluster the subjects co-occurring across the collections. These views are designed to surface discoveries that no single catalogue record makes visible. These ambitions also expose where the work is hardest. An atlas built on relationality depends on metadata that researchers often supply sparingly, subject description most of all: where terms exist, they tend to derive from Library of Congress Subject Headings, a vocabulary often poorly suited to African sources and knowledge systems. Here our thinking is still exploratory: drawing on Wikidata, and creating the African entities and concepts it lacks. Connections and keywords alike raise one question: who holds authority over how knowledge is described, and therefore found. In an era of contested truth, that is what reimagining the archive must confront.
Keywords: Africa Multiple Interactive Research Atlas; Omeka S; Metadata; Linked Data; Wikidata; Archives